Voice and image on Joao Cabral de Melo Neto's phones - Borsato, Fabiana Renata [UNESP] (Univ Federal Parana, Editora, 2020)
Joao Cabral de Melo Neto reiterates themes, images and rhythms in his poetic works. The figure of the telephone acquires plasticity to transmit both fear and death, as well as light, constancy and integrity of the city-woman, being an image present in several works of the poet. This study intends to comments on some of these poems that present the image of the telephone to understand the network of syntactic, semantic and rhythmic relations promoted by Cabral to weave the narratives of the feminine and the oneiric.
Keywords: Joao Cabral de Melo Neto; discussed poetry; rewritten